Domination, Collaboration and Conflict in Cabo Delgado's History of Extractivism - Feijó, João; Orre, Aslak (Kronos, 2024)
A long history of extractive industries and activities have shaped the societies of northern Mozambique, and the Cabo Delgado province in particular. For centuries, the growing international demand on local resources had a great impact on the northern micro-societies. The demand for cheap labour and natural resources, ranging from ivory and cotton, to timber, rubies, land, gas and more, involved thousands of local actors in its extraction, reproducing systems of local power. The persistence of poverty, inequality and conflicts, as well as simmering and sometimes grand-scale violence, fits into a long-term trend of extractivism. Through a historical approach and field observations, we focus on the political economy of extracting natural resources. We point out the persisting basic patterns of extractivism that accompanied Mozambique's integration into global markets, and continued or even deepened, in the post-independence period. These activities are oriented towards foreign markets. They are instigated by foreign investment, but invariably carried out in collaboration with a chain of national gatekeepers. In a clientelist system, local elites resort to their proximity to the state to reproduce their power, often at the expense of state expropriation. Weak state institutions have the functional effect of reproducing the elites, also serving the interests of extractivist capital. It is, however, a system with many and profound contradictions, producing conflict and violence, which also recurrently put those interests at risk.